A new species of Leptolalax (Anura: Megophryidae) from southern Vietnam - Rowley, Jodi J. L.; Le, Duong Thi Thuy; Tran, Dao Thi Anh; Hoang, Huy Duc (Zootaxa, 2011)
We describe a new species of small megophryid frog from the Langbian Plateau in southern Vietnam, the southernmost record of Leptolalax from Vietnam. Leptolalax bidoupensis sp. nov. is distinguished from its congeners by a combination of a dark brownish red ventral surface with white speckling on entire ventral surface including throat, arms and legs, small size (23.6–24.6 mm in four adult males and 29.2–29.4 mm in two adult females), bicoloured iris (coppery red upper half, fading to pale silver ventrally), a mostly smooth skin texture with no skin ridges, and relatively short tibia (male TIB:SVL 0.44–0.46). The male advertisement call of the new species, consisting of 6–9 single-pulsed notes with a dominant frequency of 1.9–3.8 kHz, is also unique among Leptolalax species for which calls are known. From the morphologically similar L. applebyi and L. melicus, L. bidoupensis sp. nov. differs by 9.3% and 9.6% sequence divergence at the 16S mtDNA gene. At present, the new species is known from montane evergreen forest between 1620–1730 m elevation, within an area of 1 km 2 . We suggest the species should be considered Data Deficient following IUCN’s Red List categories.